Nanostructured materials for lithium ion batteries - Mohd Faiz Hassan (University of Wollongong, 2012)
Lithium ion batteries have become an essential part of everyday life. They are the power source for millions of consumer, business, medical, military, and industrial appliances worldwide. To maintain lithium ion batteries as the most outstanding portable energy resources, their electrochemical performance must continue to be improved in terms of capacity, rate capability, and cycle life.